PERAN SIKAP DALAM MEMEDIASI HUBUNGAN ANTARA HARGA DENGAN NIAT BELI SMARTPHONE MEREK SAMSUNG - Putra, Putu Eka Yusdiawan; Sudiksa, Ida Bagus (E-Jurnal Manajemen; Vol 5 No 10 (2016), 2016)
The purpose of this study is to examine the effect of price toward product purchase intentions of Samsung Smartphone with attitude variable as mediating variable, study in adolescents in the city of Denpasar. Variables examined in this study is price, attitudes and purchase intention. Samples are taken as many as 100 adolescents, using non-probability sampling method in the form of purposive sampling. Data were collected through questionnaires. The analysis technique used is the Sobel test by using path analysis. Based on the analysis found that the price variable have positive and not significant to the purchase intention, the price variable have positive and significant impact to the attitudes on Samsung Smartphone product, variable attitude have positive and significant impact on the product purchase intentions, attitude variables mediate the effect of price on purchase intention Samsung Smartphone products in adolescents in the city of Denpasar.
Keywords: purchase intention, price, attitude